2011
DOI: 10.1097/01.aoa.0000406653.51348.0b
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-dependent Effects of Phenylephrine for Elective Cesarean Delivery Under Spinal Anesthesia

Abstract: A lthough use of a prophylactic phenylephrine infusion concurrently with a fluid coload can virtually eliminate hypotension associated with spinal anesthesia, maternal reactive hypertension and bradycardia are concerns. The ideal dosing regimen for a phenylephrine infusion to prevent hypotension is unknown. This double-blind, placebo-controlled study investigated the dose of phenylephrine, when given as a prophylactic fixed-rate infusion, that is associated with the fewest interventions needed to maintain mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…m -Synephrine (hydroxyl group in the meta position) is not a constituent of bitter orange nor is it present in standardized C. aurantium reference materials 22 . The m -synephrine (phenylephrine) is readily available as an over-the-counter nasal decongestant, is also used as an ophthalmic product for mydriasis, and is known for its cardiovascular effects 23 .…”
Section: Discussionmentioning
confidence: 99%
“…m -Synephrine (hydroxyl group in the meta position) is not a constituent of bitter orange nor is it present in standardized C. aurantium reference materials 22 . The m -synephrine (phenylephrine) is readily available as an over-the-counter nasal decongestant, is also used as an ophthalmic product for mydriasis, and is known for its cardiovascular effects 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Kamenik and Eržen [34] showed that CO decreases after SA in the group of middle-aged patients not receiving crystalloids as well as in the group of patients who received crystalloids before SA, while CO increases in the group of patients receiving lactated Ringer's solution at the time of spinal block. Later on, Zorko and Kamenik [35] have shown that the infusion of 1000 mL of lactated Ringer after spinal block prevented the decrease of CO after SA, CO was actually increasing while the infusion was running. In our study, we used a slightly modified hydration strategy.…”
Section: Discussionmentioning
confidence: 99%
“…La hipotensión bajo anestesia subaracnoidea en cesárea es uno de los principales eventos adversos relacionados directamente con el acto anestésico 4,5 , asociándose a importantes complicaciones tanto maternas como fetales. El objetivo de los estudios actuales está enfocado en la búsqueda del vasopresor ideal, que evite la aparición de hipotensión, considerándose el uso de la efedrina 14,15 , fenilefrina [16][17][18][19][20][21][22][23] , etilefrina. En la actualidad fenilefrina es el más usado 17 , pero no se ha podido establecer la forma ideal de administración, la dosis requerida y su presentar, pueden ser menores respecto de las dosis usadas en pacientes que no reciben profilaxis.…”
Section: Discussionunclassified
“…Se han diseñado múltiples estrategias encaminadas a reducir de forma significativa la frecuencia de presentación de hipotensión, el colocar a la gestante en decúbito lateral izquierdo para disminuir la compresión aortocava 9 , el empleo de bolos de líquidos intravenosos [10][11][12] ; la reducción de la dosis de anestésico 13 , la elevación o compresión de los miembros inferiores 9 y la administración de vasopresores [14][15][16] , son ejemplos de ello, con resultados contradictorios en su eficacia 17 . En los últimos años, ha surgido un interés particular por la administración de fenilefrina profiláctica, dado su principal efecto α adrenérgico [18][19][20] , sin embargo, los estudios realizados 21-,23 no han determinado la dosis o la forma de administración que resulte eficaz en la prevención de este evento adverso.…”
Section: Introductionunclassified